Defense diplomacy theoretical approach and practical application: Case study of the Republic of Serbia in 2013 - Milenković Aleksandar (Војно дело, 2015)
The paper introduces the concept of defense diplomacy and its relation with general diplomacy, its institutions, activities and objectives. It presents a theoretical approach to the basic principles and activities of defense diplomacy and how they were implemented in the Republic of Serbia in 2013. It analyzes in detail every aspect of defense diplomacy with an emphasis on the activities of the Ministry of Defense and the Serbian Armed Forces at bilateral, multilateral and regional levels. In particular, the paper deliberates on the aspects of military economic, sports and military education diplomatic activity. It aims to present, on the basis of public activities, the activities of the defense diplomacy of the Republic of Serbia in 2013, its achievements and accomplishments, and to give an insight into highly intensive work and activities of the Ministry of Defense and the Serbian Armed Forces in the area of foreign policy.